A study on the synthesis and magnetic properties of the cerium ferrite ceramic - Jabbarzare, Saeid; Abdellahi, Majid; Ghayour, Hamid; Arpanahi, Asiyeh; Khandan, Amirsalar (Elsevier Science Sa, 2017)
This work is a short report on the synthesis of CeFeO3 ceramic nanopowder from a mixture of CeO2 and Fe2O3 powders via a high energy ball milling process and subsequent heat treatment. Investigation of the magnetic, photocatalytic and absorption properties of CeFeO3 and its potential for colossal dielectric constant (CDC) are the main objectives of the present study. The characterization tools were X-ray diffraction (XRD), transmission electron microscopy (TEM), Field emission scanning electron microscopy (FESEM), thermogravimetry (TG), differential thermal analysis (DTA), X-ray photoemission spectroscopy (XPS), ultraviolet visible spectroscopy (UV vis) and Image-I software. According to the obtained results, CeFeO3 nanopowder can be raised as a visible light-driven photocatalyst, a semiconductor material with a narrow bandgap and a weak ferromagnetic material. For the first time the CDC behavior of this ceramic was also assessed by XPS analysis which was indicative of a good colossal dielectric constant. The results were also confirmed by the measured dielectric properties. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeFeO3; Nanopowders; Magnetic properties